Optimizing Resource Factors in Developing Coastal Area Based on Re-gional Excellences: The Case of Bekasi Regency in Indonesia - Nandang Najmulmunir, Ujang Maman, Ahya Kamilah, Dani Mulyana (International Journal of Advanced Science and Technology, 2020)
The regional development based on regional excellences – in which the community has high involvement – is a complete solution for economic community development. Therefore, by the case of Bekasi Regency in Indonesia, this research aims to identify the superiority of sub-districts in the agricultural sector, to increase the efficiency and to optimize the allocation of resources to achieve a complete economic growth and equality. For such purpose, the analysis model used in this research is Location Quotient (LQ), Regional Concentration Coefficient (RCC), Cobb-Douglas production function and optimization. The superior region and the highest value of LQ in the primary agribusiness sector in Bekasi Regency is Muara Gembong Subdistrict with milkfish ponds as the superior subsector. In the light of cobb-Douglas analysis model based on the survey data, the production factors (feed, fertilizer and pesticides, labor, and pond area) should be simultaneously increased to improve efficiency of milkfish production process; and the optimization of milkfish production could be exactly achieved by allocating certain amount of production factors.